Up and Down States and Memory Consolidation Across Somatosensory, Entorhinal, and Hippocampal Cortices - Tukker, John J.; Beed, Prateep; Schmitz, Dietmar; Larkum, Matthew E.; Sachdev, Robert N. S. (Frontiers in Systems Neuroscience, 2020)
In the course of a day, brain states fluctuate, from conscious awake information-acquiring states to sleep states, during which previously acquired information is further processed and stored as memories. One hypothesis is that memories are consolidated and stored during ‘offline’ states such as sleep, a process thought to involve transfer of information from the hippocampus to other cortical areas. Up and Down states, patterns of activity that occur under anesthesia and sleep states, are likely to play a role in this process, although the nature of this role remains unclear. Here we review what is currently known about these mechanisms in three anatomically distinct but interconnected cortical areas: somatosensory cortex, entorhinal cortex, and the hippocampus. In doing so, we consider the role of this activity in the coordination of “replay” during sleep states, particularly during hippocampal sharp-wave ripples. We conclude that understanding the generation and propagation of Up and Down states may provide key insights into the cortico-hippocampal dialogue linking archi- and neocortical areas during memory formation.